Distribution of Phenolic Acids and Antioxidant Activities of Different Bran Fractions from Three Pigmented Wheat Varieties - Jinli Zhang; Yan Ding; Haizhou Dong; Hanxue Hou; Xiansheng Zhang (Journal of Chemistry)
Phenolic acid profiles and antioxidant activities of outer bran, coarse bran, and shorts from blue, black, and purple wheat were analyzed. Phenolic acids were mainly in the bound form in pigmented wheat bran fractions. Phenolic acid content decreased in the order of outer bran, coarse bran, and shorts for the three pigmented wheat varieties. HPLC analysis of phenolic extracts demonstrated that the bound form of phenolic acids contained more ferulic, isoferulic, and p-coumaric acids compared to their free counterparts. Among the three pigmented wheat varieties, the bran fractions from blue wheat contained higher bound phenolic acids than the other two pigmented wheat bran fractions, except for purple coarse bran. The blue wheat outer bran had the highest total bound phenolic acid of 3458.71 μg/g while the purple wheat shorts had the lowest of 1730.71 μg/g. The contribution of bound phenolic acids to the total phenolic content and antioxidant activity was significantly higher than that of free phenolic acids. Blue wheat bran fractions had the highest radical scavenging activity against DPPH∙ while those of purple wheat gained the highest ABTS∙+ scavenging activity. High correlations were observed between TPC and radical scavenging capacities for DPPH and ABTS (R2>0.85, P<0.05).